2009
DOI: 10.1016/j.apm.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Using an extended activated sludge model to simulate nitrite and nitrate variations in TNCU2 process

Abstract: Keywords: TNCU2 Biological nutrient removal (BNR) Activated sludge model No. 2d (ASM2d) Ammonia oxidizing bacteria (AOB) Nitrite oxidizing bacteria (NOB) a b s t r a c t In this study, an extended activated sludge model was established to describe the transformation of nitrite ðS NO 2 Þ, nitrate (S NO 3 Þ and other components in TNCU2 process (National Central University of Taiwan No. 2) that consisted of anaerobic, oxic, anoxic, oxic zones in sequence. The significant differences between this extended model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…According to literature and our previous studies,4, 5, 9, 10, 18 oxygen consumed by X H with neither substrate nor oxygen limitation is where S O2 is the concentration of oxygen (mg L −1 ), OUR H ( t ) is the oxygen uptake rate at time t (mg O 2 L −1 h −1 ), Y H is the yield coefficient of heterotrophic biomass (mg COD mg COD −1 ), µ H is the growth rate constant for X H at any pesticide concentration (d −1 ), X H is the concentration of heterotrophic biomass (mg L −1 ) and b H is the lysis rate constant for X H at any pesticide concentration (d −1 ). The growth for X H with neither substrate nor oxygen limitation can be written as follows: Integration of Eqn (2) leads to Equation (3) can be introduced into Eqn (1).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…According to literature and our previous studies,4, 5, 9, 10, 18 oxygen consumed by X H with neither substrate nor oxygen limitation is where S O2 is the concentration of oxygen (mg L −1 ), OUR H ( t ) is the oxygen uptake rate at time t (mg O 2 L −1 h −1 ), Y H is the yield coefficient of heterotrophic biomass (mg COD mg COD −1 ), µ H is the growth rate constant for X H at any pesticide concentration (d −1 ), X H is the concentration of heterotrophic biomass (mg L −1 ) and b H is the lysis rate constant for X H at any pesticide concentration (d −1 ). The growth for X H with neither substrate nor oxygen limitation can be written as follows: Integration of Eqn (2) leads to Equation (3) can be introduced into Eqn (1).…”
Section: Methodsmentioning
confidence: 95%
“…In order to understand bacterial conversion in ASP, several mathematical models have been proposed, such as the activated sludge model (ASM)4 and the Taiwan extension activated sludge model no. 1 (TWEA1),5 and applied in our previous works 5–10. In the concept of these mathematical models, growth of microorganisms and consumption of substrate are predominated by growth rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different approaches have recently been proposed for modeling nitrification and denitrification as two-step processes. ,,, As a consequence, modeling the nitrite behavior becomes essential for the description of other processes, including P uptake . Several studies with PAOs have confirmed that elevated concentrations of nitrite would negatively affect the activities of PAOs under either anoxic or aerobic conditions, although the different threshold values of inhibition were reported. ,,, Extended activated sludge models, including two-stage nitrification, two-stage denitrification and EBPR were developed to successfully predict the behavior of nitrite and nitrate …”
Section: Introductionmentioning
confidence: 99%
“…Process rate equations(Pai 2007;Pai et al 2009b) j Process Process rate equationq i, q j C 0 [M 1 L -3 T -1 ] KNO X S KNO X S þSNO X Á XS=XH KXSþXS=XH Á X H Phosphorus accumulating organisms (PAO): X PAO SALK KALKPAOþSALK Á XPHA=XPAO KPHAþXPHA=XPAO Á XMAXÀXPP=XPAO KIPPþKMAXÀXPP=XPAO Á X PAO 13 Aerobic growth of X PAO l PAO Á SO 2 KO 2 PAO þSO 2 SNH 4 KNH 4 PAO þSNH 4 SALK KALKPAOþSALK Á XPHA=XPAO KPHAþXPHA=XPAO Á X PAO 14 Lysis of X PAO b PAO Á X PAO 15 Lysis of X PP b PP Á X PP 16Lysis of X PHA b PHA Á X PHA…”
mentioning
confidence: 99%